HUBUNGAN ANTARA KADAR HEMOGLOBIN (HB) DENGAN PRESTASI BELAJAR MAHASISWA KEBIDANAN YANG TINGGAL DI ASRAMA PENDIDIKAN STIK BINA HUSADA PALEMBANG - Sartika, Tri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Anemia in adolescents can cause physical growth retardation, behavioral and emotional disorders. This can affect the growth process and development of brain cells so that it can cause decreasing on imun system, weak easily and hunger, learning concentration disturbed, decreased learning achievement and can lead to low work productivity. According to data from Riskesdas in 2013, the prevalence of anemia in female teenagers aged 10-18 years was 57.1% and aged 19 - 45 years was 39.5%. Women have the highest risk to get anemia, especially in female teenagers. This study aims to determine the relationship between hemoglobin level (Hb) and learning achievement of midwifery students who live at Educational Dormitory of STIK Bina Husada Palembang in 2017. This study was quantitative with cross sectional approach. The study sample amounted to 84 respondents. The study instrument was Set of Hb Sahli and Checklist. Data analysis was univariate and bivariate with chi-square method. The study was conducted on 12 ? 23 June 2017. The study results showed there was significant relationship of hemoglobin levels variable with the learning achievement of Midwifery Students who lived at Educational Dormitory of STIK Bina Husada Palembang in 2017, with p value = 0.005 (? ? 0.05). The value of OR = 9,000 meant that respondents with Un-normal Hb had a chance 9 times to have Less learning achievement, compared with respondents with Normal Hb levels. It is expected that female teenagers will always maintain the reproductive health and actively seek information about reproductive health to detect early if abnormal (pathological) conditions are found.Keywords: Hemoglobin Level, Learning Achievement